1999
DOI: 10.1002/1531-8249(199905)45:5<666::aid-ana18>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variation of the inflammatory cytokine interleukin-6 delays the initial onset and reduces the risk for sporadic Alzheimer's disease

Abstract: Local inflammatory processes surrounding the amyloid plaques contribute to the progression and acceleration of the Alzheimer's disease (AD)–related neurodegeneration. Interleukin‐6 (IL‐6) is an inflammatory cytokine with possible involvement in the local immune response occurring in the central nervous system of AD patients. We tested the hypothesis as to whether a genetic polymorphism of the IL‐6 gene (IL‐6) modifies the age at onset and risk for sporadic AD. Our results support an association of the C allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
1
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(94 citation statements)
references
References 19 publications
1
89
1
3
Order By: Relevance
“…In a study on German Caucasian patients with Alzheimer's disease (AD), IL-6 minisatellite allele A5 (allele C according to the classification of Murray et al 10 ) was found to be associated with delayed onset of disease and reduced disease risk. 11 We demonstrate here that the same allele is associated with a benign course of MS. Notwithstanding their highly divergent etiologies, MS, SLE and AD share the characteristic of being conditions in which dysregulation of cytokine responses may aggravate disease.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…In a study on German Caucasian patients with Alzheimer's disease (AD), IL-6 minisatellite allele A5 (allele C according to the classification of Murray et al 10 ) was found to be associated with delayed onset of disease and reduced disease risk. 11 We demonstrate here that the same allele is associated with a benign course of MS. Notwithstanding their highly divergent etiologies, MS, SLE and AD share the characteristic of being conditions in which dysregulation of cytokine responses may aggravate disease.…”
mentioning
confidence: 52%
“…Separation of amplification products by means of denaturing PAGE on an automated DNA sequencer facilitated accurate sizing, and revealed the existence of more alleles than previously assumed on the basis of lowresolution non-denaturing electrophoresis (Table 1). [9][10][11] In order to ensure that this effect was not due to the specific phylogenetic structure of the Sardinian population, 12 we typed also a representative sample of a continentalEuropean Caucasian (Swedish) population. This revealed that the sizes and number of IL-6 minisatellite alleles were identical in both populations, although Sardinian IL-6 allele frequencies deviated strongly from the Swedish ones, as expected (P Ͻ 0.0001).…”
mentioning
confidence: 99%
“…In this regard, human evidence shows an inverse association between circulating IL-6 and mild cognitive decline in well-functioning mid-life and older persons (24,26,28). Furthermore, polymorphisms of the IL-6 gene that predict lower levels of plasma IL-6 are associated with decreased risk of developing dementia (44). However, we note that the optimized VBM procedures employed here do not reveal whether IL-6 may relate to such endpoints via neural changes in cell size, dendritic branching complexity, cell proliferation and degeneration, or even cell packing and dendritic spine density.…”
Section: Discussionmentioning
confidence: 99%
“…This SNP is also associated with systemic onset juvenile chronic arthritis (Fishman et al 1998), Alzheimer disease (Bagli et al 2000;Papassotiropoulos et al 1999), and increased bone resorption (Ferrari et al 2001). In pubertal girls, the development of peak bone density in the spine is reported to result from decreased bone resorption (but not increased bone formation), and decreased IL-6 may be in part responsible for the development of maximal peak vertebral bone mass (Manolagas 1998).…”
Section: Discussionmentioning
confidence: 99%